Planning for Fluctuating Enrollments. A Working Paper for the Annual Meeting of Post-Secondary Education Governing Boards - Minnesota Higher Education Coordinating Board, St. Paul.; Minnesota Higher Education Coordinating Board, St. Paul. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1977)
The nature and scope of the enrollment problem in Minnesota, plans and policies to deal with the problem, statewide policy implication of the problem and ways to effectively meet the challenges posed by the problem are discussed. A summary and analysis of enrollment trends in Minnesota are provided in Chapter 1, including specific projected enrollment trends for the community college system. the University of Minnesota system, area vocational-technical institutes, private collegiate institutions, and private vocational schools. Chapter 2 presents an overview of Minnesota's four public post secondary systems, private colleges, and the Minnesota Association of Private Vocational Schools plans and policies for dealing with fluctuating enrollment trends. Recommendations on planning procedures and policy development are discussed in Chapter 3. The appendices contain projected high school graduates by region, institutional enrollment projections, a summary of responses from systems and institutions for information on their plans and policies for dealing with fluctuating enrollments, and papers presented at the annual Minnesota Governing Boards Meeting. (SPG)
Availability: Minnesota Higher Education Coordinating Board, Suite 400, Capital Square Building, 550 Cedar Street, St. Paul, Minnesota 55101.
Educational level discussed: Postsecondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Bound Students; Community Colleges; Declining Enrollment; Educational Demand; Educational Planning; Enrollment; Enrollment Projections; High School Graduates; Policy Formation; Postsecondary Education; Private Colleges; State Universities; Statewide Planning; Statistical Data; Trend Analysis; Vocational Schools; Minnesota; University of Minnesota; Reports, Research